2012
DOI: 10.1089/aid.2011.0035
|View full text |Cite
|
Sign up to set email alerts
|

Virological Response and Resistance Profiles After 18 to 30 Months of First- or Second-/Third-Line Antiretroviral Treatment: A Cross-Sectional Evaluation in HIV Type 1-Infected Children Living in the Central African Republic

Abstract: A total of 242 HIV-1-infected children were followed up at the Complexe Pédiatrique of Bangui, Central African Republic, including 165 receiving antiretroviral treatment in first- (n=150) or second-/third-line (n=15) regimens. They were prospectively included in a study, in 2009, to assess their virological status and prevalence of antiretroviral drug-resistance mutations in cases of virological failure, according to revised 2010 WHO criteria (e.g., HIV-1 RNA >3.7 log(10) copies/ml). Detectable plasma HIV-1 RN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
32
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 40 publications
(52 reference statements)
6
32
1
Order By: Relevance
“…The rate of TAMs detected in our study is very high compared to previous reports among children in resource-limited settings where, as in Uganda, NNRTI-based first-line regimens are standard. 8,[20][21][22][23] This may be attributed to the fact that over half of children had a longer duration of treatment failure (i.e., longer than 1 month). Possibly, this reflects clinicians' reluctance to switch to second-line ART, due to regimen cost and subsequent loss of drug options.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of TAMs detected in our study is very high compared to previous reports among children in resource-limited settings where, as in Uganda, NNRTI-based first-line regimens are standard. 8,[20][21][22][23] This may be attributed to the fact that over half of children had a longer duration of treatment failure (i.e., longer than 1 month). Possibly, this reflects clinicians' reluctance to switch to second-line ART, due to regimen cost and subsequent loss of drug options.…”
Section: Discussionmentioning
confidence: 99%
“…A better response to second-line treatment occurs when the patient resistance profile is known before switching therapy [100]. Studies show a high rate (96.5%) of NRTI and NNRTI (98.6%) resistanceassociated mutations [100] in children failing first-line treatment in Uganda; similarly, in another study, a high rate of NNRTI (95%) and NRTI (98%) resistance-associated mutations were also observed [101] with the proportion of TAMs much higher than reported among children in other African countries [84,[102][103][104].…”
Section: Immunological and Clinical Criteria Of The Whomentioning
confidence: 93%
“…[10,11] Various factors are involved in the fact that HIV-infected children and adolescents are more vulnerable than adults to virological failure and drug resistance including the HIV resistance risk during prevention of mother-to-child transmission, [12] frequently high HIV-1 RNA plasma level in children, [13] limited number of available pediatric-formulated antiretroviral drugs for the different age classes, variable pharmacokinetics, rapid changes in body weight, frequently observed poor adherence, social environment, psychosocial factors, and frequent absence of biological monitoring. [8,1425] Thus, recent studies in African children receiving 1st-line antiretroviral treatment according to the treatment guidelines of the World Health Organization (WHO) for resource-limited countries have reported generally high degrees of virological failure depending in part on treatment duration, ranging from 6% in Kwazulu-Natal (South Africa), [26,27] 15% in Cape Town (South Africa), [28] 17% [29] to 44% [30] in Ghana, 26% in Uganda, [31] 29% in Rwanda, [32] 34% in Kenya, [33] 35% in Ivory Coast, [16] 40% in the Central African Republic, [23] 53% in rural Cameroon, [34] 55% in Senegal, [24] 56% in Togo, [25] 58% in Tanzania [35,36] to 61% in Mali. [37] In addition, circulating virus resistant to at least 1 antiretroviral drug could be detected very frequently in 61% [33] to 98% [38] of children with a detectable viral load while receiving antiretroviral treatment.…”
Section: Introductionmentioning
confidence: 99%
“…[9] Finally, several studies have reported on the outcome of antiretroviral treatment in children in Africa, but only a few reports are available on long-term outcomes and in adolescents. [19,2325,35,37,39,40] …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation